ANALISIS PENGARUH PELATIHAN PEGAWAI DAN KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN DI PT BANK BJB BATAM - Dashad Satrya Utama; Ramon Zamora (University of Riau Kepulauan, 2016)
This research was conducted at the Bank BJB Batam. The purpose of this study was to determine the effectof training and compensation for work performance together (simultaneously).In this study, the authors usecensus method with a total of 45 people to serve as respondents of the total population. While this type of dataused are primary data and secondary data. The primary data source was obtained from the questionnaire AtBank BJB competent Batam Batam BJB banks. While secondary data obtained from bank documents BJBBatam. Data collection techniques done with interviews, questionnaires and documentation. Data analysiswas performed with descriptive statistics, which is used to describe in giving an overview of the objectunder study through data taken from the population census methods obtained in the field associated withthe relevant theories and techniques of quantitative analysis of the data that has been given a scoreaccording to measurement scale used is Likert scale and the test results using SPSS (Statistical Productand Service Solution) version 20. From the results of the study authors conclude that the simultaneoustraining of employees (X1) and compensation (X2) positive and significant impact on work performance(Y), with the result 56 941 (F count) greater than 3.21 (F table).Keywords: employee training, compensation and job performance